IMPROVEMENT OF DOCUMENTATION AS AN ELEMENT OF THE METHOD ОF THE ACCOUNTING IN THE CONDITIONS OF DIGITALIZATION OF THE ECONOMY - NOVICHENKO, Lyudmila; STOIKA, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to topical issues of the development of documentation as an element of the accounting method. It has been established that the development of the information society and the digitalization of accounting lead to the modification of the content and forms of the processes of documenting the facts of economic life.  The main changes in the processes of documenting the facts of economic life through the prism of digitization and the digital economy are considered.  Changes in the content and form of documentation as an element of the accounting method in the conditions of the development of information technologies are substantiated. The main types and characteristics of electronic document management systems, which used by business entities are systematized. The advantages and disadvantages of the use of electronic document management systems by business entities are determined. It has been proven that thanks to a unified and rationally organized system of documentation of economic transactions, information is formed that ensures the subsequent adoption of relevant and urgent decisions by internal and external users for management needs. The peculiarities of the organization of electronic document circulation in the practical activity of the enterprise were studied, in particular, the proposed proposals for improving internal regulations and streamlining the use of electronic documents in order to increase the efficiency of the organization of accounting. The directions of changes and further improvement of documentation as an element of the accounting method in the conditions of digitalization of the economy are systematized. It was determined that the existence of a number of advantages of the implementation of electronic document management systems contributes to its practical use as a tool for increasing the efficiency of structural divisions and the enterprise as a whole.
Keywords: documentation; element of the accounting method; electronic document; electronic document flow; digital economy; digitization of accounting